Numbers, distribution and movements of the Nazinga elephants - Hugo Jachmann (Pachyderm)
"Outlines methods of getting information on elephant occupance and suggests both direct aerial counts and ground surveys are inaccurate due to limited visibility and uneven distribution. An alternative method of faecal dropping counts was used to assess elephant occupance on the Nazinga Ranch. Field procedures are outlined and analysis and the results discussed. Also published as ""Nombre, repartition et deplacements des elephants de Nazinga"" in Nature and Faune 1989, 5(1), p25-35."